Producing and Manipulating Information - Robert Dur; Otto H. Swank (Center for Economic Studies and ifo Institute (CESifo), 2003)
To reduce the chances of policy failures, policy makers need information about the effects of policies. Sometimes, policy makers can rely on agents who already possess the information. Often, the information has yet to be produced. This raises two problems. First, for a policy maker it is hard to ascertain how much effort an expert has put in acquiring information. Second, when the expert has an interest in the policy outcome, she may manipulate information to bring the policy decision more in line with her preferences. We show that experts who are unbiased toward the policy alternatives put highest effort in collecting information. Eliminating manipulation of information, however, requires that the preferences of the policy maker and the expert are aligned. Hence, when selecting an expert, policy makers face a trade-off. We show that policy makers optimally appoint experts with policy preferences which are less extreme than their own.
Keywords: 330